KRITERIA BADAN USAHA MILIK NEGARA YANG DIBERIKAN HAK MONOPOLI DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA - Rory Jeff Akyuwen (SASI, 2016)
Analysuing the position of monopoly State-Owned Enterprises in the perspective ofbusiness competition law which could potentially give rise to barriers in business competitionin particular concerning control over production branches are considered important andmaster his life much. Though it is excluded in law number 5 of 1999 concerning theprohibition of Monopolies and Anticompetitive Business practices are unhealthy, but thatshould not be considered a monopoly owned by the State-Owned Enterprises at the same timehave the power over the market, and all the power over its own market not obliging him tocarry on the practice of healthy competition. Criteria for State-Owned Enterprises can be given a monopoly in business competition law perspective, just look at the functions and Government intervention in the economy aimed at the earliest possible time the prosperity of the people. Criteria for State-Owned Enterprises can be given a monopoly should be seen from the form and objectives of the establishment of State-Owned Enterprises as well as the magnitude of the ownership of the Government's stake in it.